MRI Abnormalities with Febrile Status Epilepticus: The Febstat Study - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers in the FEBSTAT Study Team at centers in New York, Durham, Virginia, and Chicago, IL report MRI findings in their prospective study of the acute effects of febrile status epilepticus (FSE) in 199 children age 1 month to 5 years.